2021
DOI: 10.3390/jcm10214910
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multi-Dimensional Clinical Response Index Dedicated to Improving Global Assessment of Pain in Patients with Persistent Spinal Pain Syndrome after Spinal Surgery, Based on a Real-Life Prospective Multicentric Study (PREDIBACK) and Machine Learning Techniques

Abstract: The multidimensionality of chronic pain forces us to look beyond isolated assessment such as pain intensity, which does not consider multiple key parameters, particularly in post-operative Persistent Spinal Pain Syndrome (PSPS-T2) patients. Our ambition was to produce a novel Multi-dimensional Clinical Response Index (MCRI), including not only pain intensity but also functional capacity, anxiety-depression, quality of life and quantitative pain mapping, the objective being to achieve instantaneous assessment u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…The authors showed that health-related quality of life of male patients who perceived their jobs as “physically demanding” was more impacted by functional disability than by pain intensity. In agreement with this work, we assume that a new pain dimension should be integrated to multi-dimensional pain composite assessment [ 63 ], which will slightly change our practical approach, the objective being to propose an alternative way of work rehabilitation, along the PSPS-T2 patient pathway. Given the complexity of PSPS-T2 therapeutical approaches and, in contrast, given the need to transpose theoretical models to practical daily reality, inspiration should come from basic but robust solutions, taking country-related specificities into account.…”
Section: Discussionmentioning
confidence: 98%
“…The authors showed that health-related quality of life of male patients who perceived their jobs as “physically demanding” was more impacted by functional disability than by pain intensity. In agreement with this work, we assume that a new pain dimension should be integrated to multi-dimensional pain composite assessment [ 63 ], which will slightly change our practical approach, the objective being to propose an alternative way of work rehabilitation, along the PSPS-T2 patient pathway. Given the complexity of PSPS-T2 therapeutical approaches and, in contrast, given the need to transpose theoretical models to practical daily reality, inspiration should come from basic but robust solutions, taking country-related specificities into account.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, a significant reduction in VAS was observed at all follow-ups and the quality of life and functional capacity improved at the 1-, 3- and 6-month follow-up [ 38 ]. Objective mapping data allowed us to dissect, within adapter technology, where the added value would be and for which patient this alternative should be prioritized [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pixels of the patient’s drawing were then converted to cm², using several anatomical landmarks, patient morphology and morphometry, to optimally and accurately measure the pain area, using a patented data processing system (Patent Applications N° PCT/EP2014/067231, N° PCT/FR 14/000 186 and N° PCT/FR 14/000 187) [ 21 ]. The pain mapping software provides objective and reproducible measurements about the total pain surface and pain surface related to pain intensity expressed in cm², paresthesia coverage as the percentage of pain surface covered by paresthesia and the typology of pain ( Figure 1 ) [ 21 , 22 , 23 , 24 ]. Paresthesia coverage was considered as adequate when the paresthesia performance was greater than 60% (i.e., when at least 60% of the pain surface was covered with paresthesia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proposals have been made in relation to SCS among which are a composite score based on measures of pain intensity, pain catastrophizing, health-related quality of life, and physical capability to assess the multidimensional aspects of chronic pain, 35 a measure to represent the degree of deviation from being a holistic responder, with a total score ranging from 0 (no pain, no disability, and perfect health status) to 300 (maximal pain, maximal disability, and worst health status), 36 and a multidimensional clinical response index ranging from 0 (worst pain-related health status) to 10 (best pain-related health status) constructed from a combination of functional disability score, numeric pain-rating score, depression and anxiety score, and a mapping-intensity score. 37 Another composite approach, created to predict patient satisfaction with treatment, consists of a pain-intensity rating in the evening and interaction with walking-tolerance time. 38 …”
Section: Outcome-based Patient Selectionmentioning
confidence: 99%